(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Latent fingerprint plays an important role in forensic science as it helps in personal identification. These latent prints are trace evidences found in crime scenes which are developed and visualized using various developing methods; the one such common method of developing latent fingerprint is the powder dusting method. In this study, commercially available shikakai (Acacia concinna) powder, a naturally occurring plant-based material which acts as a gentle cleanser for hair, is used to visualize and develop latent fingerprint on various different surfaces. According to the study, the commercial shikakai powder developed latent fingerprints with distinct ridge details i.e., good fingerprint clarity on various non-porous surfaces and are compared with white fingerprint powder. The comparative analysis shows that the latent fingerprints developed using commercial shikakai powder is almost comparable with those developed using white fingerprint powder. .In conclusion, the developed fingerprints using commercial shikakai powder shows sufficient ridge details for fingerprint identification and examination and also shikakai powder’s natural makeup depicts its environmentally friendly and cost effective qualities, by making it a potential substitute for forensic purposes.